Efektivitas Inhalasi Aromaterapi Lavender terhadap Kecemasan dan Nyeri Saat Pemasangan Infus pada Anak dengan Kanker - Triana, Komang Yogi; Prihandini, Claudia Wuri; Lestari, Ni Made Pande Lilik (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2021)
Children with cancer experience various unpleasant experiences, both because of the disease and due tomedical procedures. Pediatric nurses are expected to apply the principle of atraumatic care to reduce unpleasantexperiences, such as controlling children's pain and anxiety. The aim of this study was to determine the effectof lavender aromatherapy inhalation on anxiety and pain in children with cancer who underwent infusionprocedures. This study used a quasi experimental design with non-equivalent control group design post-testonly. The sample selection used consecutive sampling at Sanglah Hospital Bali, involving 60 respondents. Theresults showed that lavender aromatherapy intervention had a significant effect on pain during infusionprocedures in children with cancer with a p value = <0.0001 (<0.05), but different results were shown inchildren's anxiety with p value = 0.523 (> 0, 05). Thus, aromatherapy intervention can be used as one of theinterventions that nurses can do in the ward to implement the Complementary Alternative Medicine (CAM) forpain management in children during invasive procedures.